Injury survey in competitive sub-elite rhythmic gymnasts: results from a prospective controlled study - Cupisti, A.; D'Alessandro, C.; Evangelisti, I.; Umbri, C.; Rossi, M.; Galetta, F.; Panicucci, E.; Lopes Pegna, S.; Piazza, M. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to determine the frequency, anatomical site and types of injury incurred in rhythmic gymnastics. Methods: An 8-month prospective and controlled injury survey was planned, including 70 club-level competitive rhythmic gymnasts, aged 13-19 years. Information on injury events was recorded weekly in an injury record booklet for any event occurring over that week. Height, weight, anthropometric measurements and time spent in physical activity were recorded at baseline. Data from 72 age-matched non-athletic females served as controls. Results: Forty-nine significant injuries were reported by gymnasts and 34 by controls (70% vs 47%, P<0.005, odds ratio 2.28); gymnasts sustained a rate of 1.08 injuries per 1 000 h of training. The most prevalent anatomical sites sustaining injury were the ankle and the foot (38.9%), followed by back (22.2%). Strains and sprains were frequently reported both in gymnasts and in controls. Gymnasts missed an average of 4.1 days of physical activity as compared to 18.9 days for the control females. Alternatively, modification of training sessions occurred more frequently for the gymnast group (32 vs 7 cases for controls). The total school days missed were lower for the injured gymnasts than for the injured controls (27 vs 64 days). Conclusion: Competitive, club-level rhythmic gymnastics show a higher prevalence of injuries than non-athletic controls, but considering the high number of hours spent in training sessions, it derives that rhythmic gymnasts is a sport discipline at relatively low risk of severe injuries. These are mainly limited to back and lower limbs, are generally not severe and do not significantly hinder the preparation for the competitions.